Evolving stability and pH-dependent activity of the high redox potential Botrytis aclada laccase for enzymatic fuel cells. Issue 1 (December 2017) - Scheiblbrandner, Stefan; Breslmayr, Erik; Csarman, Florian; Paukner, Regina; Führer, Johannes; Herzog, Peter; Shleev, Sergey; Osipov, Evgeny; Tikhonova, Tamara; Popov, Vladimir; Haltrich, Dietmar; Ludwig, Roland; et al.
Abstract Fungal high redox potential laccases are proposed as cathodic biocatalysts in implantable enzymatic fuel cells to generate high cell voltages. Their application is limited mainly through their acidic pH optimum and chloride inhibition. This work investigates evolutionary and engineering strategies to increase the pH optimum of a chloride-tolerant, high redox potential laccase from the ascomyceteBotrytis aclada . The laccase was subjected to two rounds of directed evolution and the clones screened for increased stability and activity at pH 6.5. Beneficial mutation sites were investigated by semi-rational and combinatorial mutagenesis. Fourteen variants were characterised in detail to evaluate changes of the kinetic constants. Mutations increasing thermostability were distributed over the entire structure. Among them, T383I showed a 2.6-fold increased half-life by preventing the loss of the T2 copper through unfolding of a loop. Mutations affecting the pH-dependence cluster around the T1 copper and categorise in three types of altered pH profiles: pH-type I changes the monotonic decreasing pH profile into a bell-shaped profile, pH-type II describes increased specific activity below pH 6.5, and pH-type III increased specific activity above pH 6.5. Specific activities of the best variants were up to 5-fold higher (13 U mg−1 ) thanBa L WT at pH 7.5.